Fiscal Mechanism for Countering Negative Environmental Externalities - Viktor Melnyk; Vadym Hrebenozhko (Journal of Vasyl Stefanyk Precarpathian National University)
The article analyzes approaches to defining the fiscal mechanism. The authors presented its essence from the perspective of the concept of sustainable development, and also revealed its role in counteracting negative environmental externalities and adapting to climate change. It is determined that the state's use of the fiscal mechanism to ensure the conditions for sustainable development of society is carried out using its components, each of which is aimed at achieving a certain goal and objectives of forming an eco-socio-economic system through fiscal relations. In the structure of the fiscal mechanism as a hierarchical system, such relatively independent components (subsystems of the second order) are distinguished as the mechanism for accumulating budget revenues (in combination with tax, credit (loan), domain-regalia mechanisms), the expenditure-budget mechanism (as a set of the budget expenditure mechanism and the mechanism for repaying state and local debts). The theoretical analysis of issues of countering negative environmental externalities allowed us to classify specific instruments and levers of the fiscal mechanism into the following groups:budget expenditures of different levels intended to counter negative environmental externalities and adapt to climate change, namely, state and municipal loans and investments in green economy facilities, green economy subsidies, direct financing of environmental protection measures; specific tax instruments of environmental focus (energy and fuel taxes; transport taxes; taxes on emissions that cause global changes; payments for pollution, waste disposal and recycling, for the use of natural resources and subsoil, for noise impact, etc.); non-tax revenue instruments (revenues from auctions of emission permits); loan instruments of environmental focus (green bonds, sustainable development bonds, climate bonds issued by state and local authorities); quasi-fiscal instruments (international and intergovernmental grants and assistance (including within the framework of international climate initiatives), national climate initiatives).